PENGARUH PENGGUNAAN VIDEO PEMBELAJARAN MATEMATIKA BERMUATAN KEARIFAN LOKAL DALAM APLIKASI ZOOM TERHADAP PRESTASI BELAJAR MATEMATIS MAHASISWA - Ferdinandus Ardian Ali; Emilianus Jehadus; Kristianus Viktor Pantaleon; Bedilius Gunur (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research was conducted to measure the effectiveness of using mathematics learning videos containing local wisdom during lectures through the Zoom application, and was conducted in the odd semester of the 2020/2021 academic year at the campus of the Santu Paulus Ruteng Catholic University of Indonesia. The instrument used was a test, and data collection was done by giving a test description. Hypothesis I was tested using paried sample test, while hypothesis II was tested using independent sample test. The results showed that in the experimental group the pre-test average was 76,32 and the post-test average was 85,63, while in the control group the pre-test average was 76,95 and the post-test average was 79,00. Homogeneity and normality test results obtained data homogeneous and normally distributed. Hypothesis I test results obtained sig value. = 0,000 <0,05 so that H0 is rejected H1 is accepted, meaning that there is a difference in the mean pre-test and post-test mean in the experimental group, where there is an increase in the average student's mathematical learning achievement of 9,31. Hypothesis II test results obtained sig value = 0,000 <0,05 so that H0 is rejected H1 is accepted, meaning that there is a difference in the average mathematical learning achievement in the experimental group with the control group, where the experimental group is higher than the control group. Thus it is concluded that the use of mathematics learning videos that contain local wisdom during lectures through the Zoom application is effective.